2019
DOI: 10.1093/ofid/ofz309
|View full text |Cite
|
Sign up to set email alerts
|

Shedding and Transmission Modes of Severe Fever With Thrombocytopenia Syndrome Phlebovirus in a Ferret Model

Abstract: Background Although human-to-human transmission of severe fever with thrombocytopenia syndrome phlebovirus (SFTSV) via direct contact with body fluids has been reported, the role of specific body fluids from SFTSV-infected hosts has not been investigated in detail. Methods To demonstrate the virus transmission kinetics in SFTSV-infected hosts, we adapted the ferret infection model, and evaluated the virus shedding periods, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…Previous studies demonstrated that aged ferrets mimic clinical signs (fever, hematological changes) of human SFTSV infection (27)(28)(29). Further, severe illness was exhibited only in aged ferrets, which is similar to that seen in humans older than 60 years.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies demonstrated that aged ferrets mimic clinical signs (fever, hematological changes) of human SFTSV infection (27)(28)(29). Further, severe illness was exhibited only in aged ferrets, which is similar to that seen in humans older than 60 years.…”
Section: Discussionsupporting
confidence: 55%
“…) was inoculated into young adult and aged ferrets, a proven SFTSV infection model (27)(28)(29), and clinical symptoms, hematology, and mortality were monitored for 14 days. To optimize the infection dose in ferrets, we analyzed the growth property of each selected virus in Vero E6 cells (Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Ferret studies have shown that SFTSV can be transmitted in the absence of ticks between co-housed ferrets or ferrets co-housed with a separator (23). The detection of SFTSV in ferret saliva, feces, and urine suggests that these fluids are a likely route of SFTSV transmission in the absence of ticks (23). Indeed, one report indicates that SFTSV can spread between humans in a nosocomial setting through contact with patient blood (24).…”
Section: Introductionmentioning
confidence: 99%
“…In Bunyavirales , interhuman transmission was reported between households of ANDV in Argentina and Chile [ 22 , 23 ]. Dabie bandavirus from SFTSV-positive urine samples was transmitted to ferrets [ 24 ]. Although there is no report that human-to-human transmission of HTNV occurs through patient excreta, the risk of infection through urine or saliva still remains.…”
Section: Discussionmentioning
confidence: 99%